Application of Theory of Planned Behavior on Sexual Behavior in Female Adolescents - Tri Ayu Setiowati; Eti Poncorini Pamungkasari; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: In Indonesia, someone starts having a relationship for the first time in their teens. A woman starts having a relationship at the age of 15-17 years (33.3%). In addition, a man starts having a relationship at the age of 15 years (34.5 %). Sex behavior in adolescents had high consequences in physical and psychosocial health problems. The purpose of this study was to determine sexual behavior in female adolescents using Theory of Planned Behavior.Subjects and Method: This was a cross-sectional study conducted in Bantul, Yogyakarta, from June to July 2019. A sample of 200 female adolescents was selected by sample using random sampling. The dependent variable was sexual behavior. The independent variables were intention, attitude, subjective norm, perceived behavioral control, behavioral belief, normative belief, and control belief. The data were collected by questionnaire and analyzed by path analysis.Results: Positive sexual behavior in female adolescents was directly and positively affected by intention (b= 3.22; 95% CI= 1.46 to 4.97; p<0.001) and perceived behavioral control (b= 2.42; 95% CI= 1.23 to 3.61; p<0.001). Positive sexual behavior was indirectly affected by attitude, subjective norm, perceived behavioral control, behavioral belief, normative belief, and control belief.Conclusion: Positive sexual behavior in female adolescents is directly and positively affected by intention and perceived behavioral control. It is indirectly affected by attitude, subjective norm, perceived behavioral control, behavioral belief, normative belief, and control belief.Keywords: sexual behavior, adolescents, Theory of Planned Behavior, path analysisCorrespondence: Tri Ayu Setiowati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: triayu.setiowati@gmail.com. Mobile: 085329680266.Journal of Health Promotion and Behavior (2019), 4(2): 126-136https://doi.org/10.26911/thejhpb.2019.04.02.05